2021
DOI: 10.1038/s41598-021-87706-w
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperoxia-activated circulating extracellular vesicles induce lung and brain injury in neonatal rats

Abstract: Hyperoxia-induced lung injury plays a key role in the development of bronchopulmonary dysplasia (BPD), characterized by inflammatory injury and impaired lung development in preterm infants. Although BPD is a predictor of poor neurodevelopmental outcomes, currently it is uncertain how lung injury contributes to brain injury in preterm infants. Extracellular vesicles (EVs) are a heterogeneous group of cell-derived membranous structures that regulate intercellular and inter-organ communications. Gasdermin D (GSDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…EVs have been implicated in physiological and pathological communication between cells inside the same organ and between distant organs [ 9 , 13 ]. EVs can be classified according to their size, production mechanisms, and contents [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs have been implicated in physiological and pathological communication between cells inside the same organ and between distant organs [ 9 , 13 ]. EVs can be classified according to their size, production mechanisms, and contents [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In traumatic brain injury, EVs have been shown to contain inflammasome proteins, whose activation can lead to acute lung injury [ 12 ]. More recently, we have shown that circulating EVs from newborn rats exposed to hyperoxia contain inflammasome proteins that can induce lung and brain inflammation when transfected into normal animals [ 13 ]. These exosomes also contained gasdermin D (GSDMD)—a molecule downstream from caspase-1—that is the effector of pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, plasma exosomes of patients with burn injury are enriched with the S100 calcium binding protein A9 (S100A9), which inhibits the expression of zonula occludens-1 (ZO-1) and occludin, and activates the p38 MAPK signaling pathway in human pulmonary microvascular endothelial cells (HPMECs), ultimately leading to the disruption of the tight junctions and endothelial barrier [ 81 ]. Similarly, plasma EVs of hyperoxia-exposed rats revealed increased levels of surfactant protein C and GSDMD-p30, and their injection into new-born rats induced inflammatory injury and cell death in pulmonary vascular endothelial cells [ 85 ].…”
Section: Role Of Evs In Regulating Alveolar Cells In Ali/ardsmentioning
confidence: 99%
“…Furthermore, increased proinflammatory cytokines and decreased VEGF expression in lung tissues correlated with reduced brain weight, supporting the hypothesis that lung injury may aggravate adverse neurodevelopmental outcome [ 45 ]. A recent study revealed that extracellular vesicles/exosomes released from AECII cells in hyperoxia-injured lungs induced lung and brain injury when adoptively transferred into naïve neonatal rats [ 46 ]. The authors suggested that these extracellular vesicles/exosomes may enter the circulation, subsequently cross the BBB, and induce inflammatory brain injury [ 46 ].…”
Section: Effect Of Hyperoxia On Vascular Formation and Structural Rem...mentioning
confidence: 99%
“…A recent study revealed that extracellular vesicles/exosomes released from AECII cells in hyperoxia-injured lungs induced lung and brain injury when adoptively transferred into naïve neonatal rats [ 46 ]. The authors suggested that these extracellular vesicles/exosomes may enter the circulation, subsequently cross the BBB, and induce inflammatory brain injury [ 46 ]. These studies support the hypothesis of a detrimental interaction between lung and brain injury caused by hyperoxia.…”
Section: Effect Of Hyperoxia On Vascular Formation and Structural Rem...mentioning
confidence: 99%